Research of a new hot-rolled connector connection to composite walls. (September 2022) - Yu, Yujie; Tian, Peifeng; Lin, Siwen; Wang, Xiaoxiang; Wei, Biao; Jiang, Lizhong
Abstract: The composite members in steel residential buildings often possess small sections and have high restrictions on the indoor space extrusion of structural components, and then traditional diaphragm type and internal or exterior stiffener connections are hardly applied. A new hot-rolled connector connection was proposed, which used the flange-to-web arch transition of hot-rolled steel beams as the intermediate connector. The smooth section transition of the connector at the column face junction can reduce the stress concentrations and premature fracture potentials of connections between H-shaped beams and small-size composite walls or CFST columns in steel residential buildings. Four hot-rolled connector connections with different connector designs and beam sizes were tested under cyclic loads, and the seismic performances and working mechanisms were investigated. Refined finite element simulations were performed to indicate the load transfer path and load sharing mode in the connection. Results indicated that the proposed connection displayed plump hysteretic relations and satisfactory energy dissipation ability. The strengthened connectors succeeded in inducing the high plasticity away from the wall or column face. The bottom beam flange to connector butt weld was prone to fracture. The HTC connection with a long HTC connecting beam and the two bolt-row construction as the web connection was suggested.